More self-organization, more control – or even both? Inverse transparency as a digital leadership concept - Maren Gierlich-Joas; Thomas Hess; Rahild Neuburger (Business Research, 2020)
Digital innovations drive an organization's digital transformation. While numerous studies focus on digital product and service innovation, digital process innovation and novel business models, management and leadership concepts are primarily investigated as enabling framing conditions in previous contributions. However, management and leadership concepts have changed dramatically in the digital era. The rise of digital technologies has led to companies acquiring large amounts of data. Moreover, novel technical solutions facilitate the analysis and processing of this data, leading to an increase in organizational transparency. Traditional leadership theories fail to explain the influence of digitalization and increasing transparency of leadership. In a digitized world, managers often face a trade-off when using data for management purposes. On the one hand, transparency leads to decreasing information asymmetries, allowing managers to monitor employees' actions at low cost. On the other hand, employees demand self-organization and empowerment. In this context, new forms of control and employee engagement need to be designed. With our conceptual paper, we aim to provide a solution to the challenges of using transparency in leadership in a mutually beneficial way for managers and employees by introducing the concept of "inverse transparency." We develop the concept building on the existing literature on transparency and leadership. We see inverse transparency as the basis for a new type of digital innovation, which we introduce as digital leadership innovation. Thus, we enhance current research on leadership approaches and digital innovation and create a theoretical basis for further research.
Keywords: 650; Digital innovation; Digital transformation; Leadership Transparency; Empowerment; Inverse transparency